Development of a Monitoring Environment for a Large-scale Surface-Flow Constructed Wetland. Issue 7 (2022) - Maurice, Nicolas; Pons, Marie-Noëlle; Adouani, Nouceiba; Pochet, Cécile
Abstract: The instrumentation implemented to monitor a large-scale surface-flow constructed wetland (6 ha) devoted to reclaimed wastewater improvement and urban rainwater treatment is described and discussed. Flowmeters, conductimeters, light sensors, fluorometers and automated cameras have been deployed to provide information on flow patterns, water quality and vegetation. The latter is also monitored by remote sensing with satellite imagery.